Gambaran Tingkat Pengetahuan Orang Tua tentang Demam Berdarah Dengue (DBD) - Wira Setyawati Zendrato; Bistok Saing; Wilson Riau (Jurnal Kedokteran Methodist, 2024)
Background: Dengue Hemorrhagic Fever (DHF) is one of the most common public health problems in Indonesia. Dengue Hemorrhagic Fever is an infectious disease caused by dengue virus. In 2015, there were recorded 126,675 DHF patients in 34 provinces in Indonesia, and 1,229 of them died. The number is higher than the previous year, which is as many as 100,347 people with DHF and as many as 907 patients died in 2014. Method: This research is a descriptive study with a large sample of 95 respondents with the location of research in Merdeka Village, Medan New District, Medan City. The study began on June 22 - July 04, 2017 and data was collected through the distribution that have validation. Results: The results showed that of the 95 respondents, majority 40 people (42.1%), had sufficient knowledge about Dengue Hemorrhagic Fever (DBD), 37 people (42.1%), had good knowledge about DBD and 18 people (18.9%)had less knowledge about DBD. Conclusion: Based on this research, it can be concluded that generally levelof parent knowledge about DBD including enough category. Parents who have a good knowledge of the source of information from health workers counseling.